Premium diets: acceptance and feeding behavior in adult dogs (Canidae) (UNED Research Journal, 2025)
Introduction: The dog food industry has grown significantly, leading to trends like premium foods. With high demand and costs, assessing palatability is essential for ensuring positive animal reception. Currently, there are few studies of this type in Costa Rica. Objective: To evaluate adult dogs' acceptance and feeding behavior towards two premium commercial foods. Methods: We studied eight adult large-breed female dogs, feeding them three diets at various stages of the research: Control (used to “wash out” between tests), A, and B (premium diets). We used one-bowl tests for acceptance, and two-bowl tests for preferences. We used direct observation and videos to record behavior. Results: We did not find significant differences in the palatability tests. However, there were differences (p < 0.05) in the consumption speed in both tests, with Diet B being consumed faster (one bowl = 2.80 min; two bowls = 10.04 min) than Diet A (one bowl = 6.18 min; two bowls = 22.06 min). Additionally, there was a tendency to prefer consuming Food B first. The animals did not exhibit behavioral alterations. Conclusion: Both diets were highly palatable, but consumption favored food B. Over time, many of the observed behaviors decreased as the animals developed a routine.
Keywords: dog nutrition; commercial diets; palatability tests; animal conduct; Canis lupus familiaris